2015
DOI: 10.1590/1089-6891v16i319865
|View full text |Cite
|
Sign up to set email alerts
|

SEROLOGICAL EVIDENCE OF EXPOSURE TO <italic>Anaplasma phagocytophilum</italic> IN HORSES FROM THE RIO DE JANEIRO STATE MOUNTED POLICE BRED IN THE URBAN ZONE

Abstract: <title>Abstract</title><p><italic>Anaplasma phagocytophilum</italic> is an emergent hemoparasite in regions where ticks are regularly found. In order to investigate the rate of anti-<italic>A. phagocytophilum</italic> antibody in horses of the Mounted Police of Rio de Janeiro state and therefore the presence of this agent, 41 horses from the Cavalry Squadron (CS) and 50 from the Regiment of Mounted Police (RMP) were selected. For the serologic diagnosis the Indirect Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…We confirmed a 42.5% prevalence of antibodies to A. phagocytophilum. Consistently with the results obtained by Rolim et al (2015), no predisposition for infection based on the animal's sex or age was observed in our study, and no molecular evidence of A. phagocytophilum was found in the animals tested. In Europe, a seropositivity higher than this was observed only in the Czech Republic (Praskova et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…We confirmed a 42.5% prevalence of antibodies to A. phagocytophilum. Consistently with the results obtained by Rolim et al (2015), no predisposition for infection based on the animal's sex or age was observed in our study, and no molecular evidence of A. phagocytophilum was found in the animals tested. In Europe, a seropositivity higher than this was observed only in the Czech Republic (Praskova et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…Anti- A. phagocytophilum antibodies were detected in 65% ( n = 13) of horses in the Brazilian Army (1st Guards Cavalry Regiment, Independence Dragoons, Brasilia - DF, Brazil) and in Goiania county, GO, Brazil, with clinical signs suggestive of EGA ( Salvagni et al., 2010 ). Anti- A. phagocytophilum antibodies were also detected in horses from the Southeast ( Prado et al., 2018 , Rolim et al., 2015 ), Northeast ( Nogueira et al., 2017 ) and South ( Vieira et al., 2013 ) of Brazil. In addition, Sacchi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Serological studies were performed in Brazil to verify the presence of anti- A. phagocytophilum IgG antibodies. Those reports identified high titers in horses from the states of São Paulo ( Salvagni et al., 2010 ) and Rio de Janeiro ( Rolim, Oliveira, & Brasil, 2015 ), in dogs from Paraná ( Vieira et al., 2013 ) and in a deer marsh ( Blastocerus dichotomus) ( Sacchi, Duarte, André, & Machado, 2012 ). Santos et al.…”
Section: Introductionmentioning
confidence: 99%
“…Recently in Brazil, Rolim et al (2015) investigated the rate of anti-A. phagocytophilum antibodies in horses from the Cavalry Squadron and Regiment of Mounted Police and found out 12% (11/91) animals with titer≥1:80.…”
Section: Discussionmentioning
confidence: 99%